2017
DOI: 10.1016/j.media.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

ShapeCut: Bayesian surface estimation using shape-driven graph

Abstract: A variety of medical image segmentation problems present significant technical challenges, including heterogeneous pixel intensities, noisy/ill-defined boundaries and irregular shapes with high variability. The strategy of estimating optimal segmentations within a statistical framework that combines image data with priors on anatomical structures promises to address some of these technical challenges. However, methods that rely on local optimization techniques and/or local shape penalties (e.g., smoothness) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Currently, our study is among the few that have attempted at direct automatic segmentation of the LA from LGE-MRIs [14,46,47]. Out of all existing attempts, most of the LGE-MRI studies, either in-vivo or ex-vivo, have relied heavily on manual segmentation [9,[48][49][50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, our study is among the few that have attempted at direct automatic segmentation of the LA from LGE-MRIs [14,46,47]. Out of all existing attempts, most of the LGE-MRI studies, either in-vivo or ex-vivo, have relied heavily on manual segmentation [9,[48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…A benchmark study published by Tobon-Gomez et al compared the performance of nine different algorithms for LA segmentation from non-gadolinium enhanced MRIs/CT and showed that methodologies combining statistical models with regional growing approaches were the most effective [13]. Similar techniques have also been proposed and further improved upon for segmenting the LA from LGE-MRIs in studies by Veni et al [14], Zhu et al [15] and Tao et al [16]. Despite these recent efforts, most of the existing structural analysis studies, especially those that utilize clinical LGE-MRIs, are still based on laborintensive and error-prone manual segmentation approaches [9,10,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the limited number of submitted algorithms, the study was not able to draw any definitive conclusions in terms of approach development. Other studies on LGE-MRI segmentation also have limited efficacy as the methods proposed require additional information such as manually initialized shape priors (Veni, Elhabian andWhitaker 2017, Zhu et al 2013) or paired magnetic resonance angiography (Tao et al 2016). While LGE-MRI segmentation still heavily relies on traditional methods, many recent advancements in CNNs have been made for image segmentation in general.…”
Section: Related Workmentioning
confidence: 99%
“…The boundary term in these works was normally defined according to the dissimilarity of intensity and distance between two connected nodes. Veni et al (2017) designed a regional term based on a generative image model incorporating both local and global shape priors. The boundary term was defined for regularizing the smoothness of the estimated surface, i.e., minimizing the squared difference of the offsets between neighboring vertices.…”
Section: Graph Formulation For Scar Segmentationmentioning
confidence: 99%